Mini Core Collection as a Resource to Identify New Sources of Variation. Issue 6 (1st November 2013) - Upadhyaya, H.D.; Dronavalli, N.; Dwivedi, S.L.; Kashiwagi, J.; Krishnamurthy, L.; Pande, S.; Sharma, H.C.; Vadez, V.; Singh, S.; Varshney, R.K.; Gowda, C.L.L.
ABSTRACT: In chickpea, bottlenecks associated with its domestication and low use of germplasm in improvement programs have resulted in a narrow genetic base and its vulnerability to abiotic and biotic stresses. The core and mini core collections, representing diversity in the entire collection, have been advocated for enhanced utilization of germplasm in crop improvement. A chickpea mini core (211 accessions) was evaluated for agronomic traits from 2000 and 2001 to 2003 and 2004 in post‐rainy seasons under irrigated and non‐irrigated conditions. The published information on the response of chickpea mini core accessions to stress revealed that 40 accessions had resistance to abiotic stress, 31 to biotic stress, and 24 had no resistance to either of the stresses. The abiotic and biotic stress resistant groups had six accessions in common. The mini core collection accessions were also a part of composite collection accessions in chickpea, which was genotyped using 48 simple sequence repeats (SSRs; BMC Plant Biol. 8:106, 2008). The agronomic evaluation, stress response, and molecular profiling data on 93 accessions, including four controls, were used to identify genetically diverse germplasm with agronomically beneficial traits. A number of genetically diverse accessions possessing agronomically beneficial traits, such as ICC 440, 637, 1098, 3325, 3362, 4872, 7441, 8621, 9586, 10399, 12307, 14402, 15680, and 15686, which meet breeders' needs, have been identified for use in breeding and genetics to map genomic regions associated with beneficial traits and as source materials for developing high yielding and widely adapted chickpea cultivars with multiple resistance to abiotic and biotic stress.